Energy Risk Management and Cost of Economic Production Biodiesel Project - Romprasert, Suppanunta; Jermsittiparsert, Kittisak (International Journal of Energy Economics and Policy, 2019)
Although electricity in Thailand is still sufficient to provide services, but there may be a risk in future from relying solely only on oil energy. Therefore, alternative energy is a good way to distribute fuel. The growth rate of community brings higher levels of imported energy from foreign countries including expansion of large projects resulting in opening of exploration and production rights for petroleum to increase energy security and reduce domestic risks. This research aims study of economic production cost analysis for community biodiesel production from remained kitchen oil case of community management. The collecting information is on price and use of raw materials for biodiesel production to calculate. According to studies, it has been found that total variable cost of biodiesel production process for 1st time is equal to 33.42 baht per liter comparing to 2nd time on total variable cost only 23.62 baht per liter. Most of variable cost for 2nd time is used kitchen oil representing 51 percent of total cost price. This research analyzed production potential for the use of biodiesel B100 reflecting on reduction of diesel used in community's agricultural machine. It was found that community has potential to produce biodiesel for their own use causing savings within community around 134,220 baht per year if community produce 1,500 liters. If the government encourages community members to understand and produce biodiesel for themselves, it will be able to reduce oil imports many million baht and overall positive impact on economic, social and environmental sectors of Thailand. Keywords: Community Management, Cost Analysis, Economic Production, Energy Risk JEL Classifications: Q55, D20 DOI: https://doi.org/10.32479/ijeep.8367